Legislation on Teacher Training, the cases of Valencia, Spain and Chiapas, Mexico - Nájera Utrilla, Joaquín Octavio; Santiago García, Rosana; Peiró i Gregòri, Salvador (Atenas, 2017)
The pedagogical technical advisor (ATP) has the function of forming teachers of basic education in service through courses, in a continuous fashion, interested in how they develop their functions and the regulatory framework that governs them. This article gives the reader data about the role of the ATP and reviews two regulatory frameworks in this case, specifically from Spain and Mexico, both educational systems have organizational similarities on permanent teacher training. This analysis is part of Investigation called the Pedagogical Competencies Technical Advisor basic education in Tsotsil - Tseltal Altos Region of Chiapas.